TINGKAT KESADARAN MASYARAKAT DALAM PERENCANAAN KEUANGAN KELUARGA DI DAERAH KECAMATAN MEDAN LABUHAN - Edi Saputra Matondang (Cattleya Darmaya Fortuna, 2020)
Indonesia as one of the largest countries in the world has very large natural and human resources, so manycountries want to invest in this country due to the huge market share. But this large market share does notindicate that the community is good in its financial management. This is evidenced by the results of a survey byOJK in 2016 that Indonesia's financial literacy rate is 29.7% and Indonesia's financial inclusion rate is 67.8%.This is the main attraction for the authors to conduct research on the level of public awareness in family financialplanning in the Medan Labuhan District because this area is a potential area besides the very large communitybut this area is also already an area where many people work as fishermen.